The Influence of Gadgets on The Development of The Early-Age Learners’ Behavior and Character - Ni Nyoman Kurniawati; I Made Sutharjana (International Journal of Multidisciplinary Sciences, 2023)
This article aims to determine the effect of gadgets on the development of early-age behavior and character, as well as the implementation of its solutions. Gadgets are modern communication tools and make it easier for human communication. There are many types of gadgets: mobile phones, iPad or tablets, netbooks, digital cameras, laptops or computers, and smartwatches. Early age is children aged 0 to 6 years. The research method used is a literature study. The results of the study show that gadgets have an influence on the development of behavior and character of early-age learners. Excessive use of gadgets has a negative impact on the development of children's behavior and character, the children become introverted individuals, less interact with others, don't care about their surroundings, don't know social ethics, and essay gets angry and even have tantrums. Solutions for gadget addiction to the development of the child’s behavior and character include limiting usage time, giving a schedule, not giving full access, setting a good example, setting a gadget-free area at home, and informing about the dangers of using gadgets for too long so that gadgets don't have a bad effect on the development of behavior and character of the children